Lead extraction of an unintentional pacemaker lead implantation in the left ventricle from the left subclavian artery. Issue 2 (17th November 2021) - Strubé, Camille; Domain, Guillaume; Dognin, Nicolas; Dagenais, François; Plourde, Benoit; Jacques, Frédéric; Gilbert, Philippe; Steinberg, Christian; Philippon, François
Abstract: Introduction: Inadvertent implantation from the subclavian/axillary arteries is uncommon and has been rarely reported. Complications are frequent, mainly driven by thromboembolic events. Lead extraction, depending on the dwell time may be challenging and associated with thromboembolic events Case Report: We report the case of an 87‐year‐old man who had involuntarily pacemaker lead implanted into the left ventricle through the left subclavian artery. An extraction procedure was performed with surgical dissection to the artery and simple traction of the probe without complication. Conclusion: Percutaneous lead extraction using surgical dissection is a therapeutic option for less than one year old left ventricle inadvertent lead implantation.